Factors associated with asymptomatic COVID-19 patients in Petaling District, Selangor, Malaysia - Lim, Kuang Kuay; Ainul Nadziha Mohd Hanafiah,; Lee, Soo Cheng; Chan, Ying Ying; Mohd Shaiful Azlan Kassim,; Chong, Zhuo Lin; Roslinda Abu Sapian,; Nurul Syarbani Eliana Musa,; Ridwan Sanaudi,; Mohamed Paid Yusof, (Penerbit Universiti Kebangsaan Malaysia, 2021)
The rapid spread of the Coronavirus disease 2019 (COVID-19) worldwide has led the World Health Organization to declare COVID-19 outbreak as a pandemic on March 11, 2020. As the local studies on factors leading to the absence or presence of clinical illness among the COVID-19 cases are sparse, the study aims to determine the factors associated with asymptomatic COVID-19 patients in Petaling District, Selangor, Malaysia. Data on COVID-19 patients were extracted from the database of confirmed cases in Petaling District Health Office, Selangor, Malaysia from 3rd February 2020 to 30th April 2020. An asymptomatic laboratory-confirmed case is a person infected with COVID-19 who does not develop any symptoms. The study included socio-demographic variables, the detailed information on clinical manifestations and co-morbidity of the patients. Descriptive and multiple logistic regression analyses were conducted to determine the factors associated with asymptomatic patients. The overall COVID-19 patients in Petaling District were 434. Approximately 70% (n= 292) of the patients were symptomatic while 32.7% (n= 142) were asymptomatic. Multivple logistic regression analyses revealed that factors significantly associated with asymptomatic patients were age below 40 years old (aOR: 1.79, 95% CI 1.11, 2.86), non-Malaysians (aOR: 3.22, 95% CI 1.44, 7.19) and local cases (aOR: 2.51, 95% CI 1.42, 4.42). Gender, ethnicity, co-morbidity and township were not significantly associated with asymptomatic patients. Approximately one-third of COVID-19 patients were asymptomatic and the risk factors identified were younger age, non-Malaysians and local cases. Rigorous epidemiological investigation is helpful in identifying COVID-19 cases among these group of people who are asymptomatic.